The effect of person‐centred communication on parental stress in a NICU: a randomized clinical trial. (16th September 2013) - Weis, J; Zoffmann, V; Greisen, G; Egerod, I
Abstract Aim To investigate the effect of the Guided Family‐Centred Care intervention, developed by the lead author, on parental stress in a neonatal intensive care unit (NICU). Methods Parents (n = 134) of infants born ≤34 weeks gestational age were randomly assigned to a standard care group (n = 60) or intervention group (n = 74) between April 2011 and August 2012. Guided Family‐Centred Care components used were as follows: scheduled nurse–parent dialogues, semi‐structured reflection sheets and person‐centred communication. Parental stress was assessed at discharge using parent‐reported outcomes on the Nurse Parent Support Tool and the Parental Stressor Scale: Neonatal Intensive Care Unit. Results The total stress scores reported by parents did not vary significantly between the intervention and standard groups, with a mean (SD) of 2.70 (0.67) versus 2.84 (0.71), respectively. However, the confidence interval included the prespecified clinical significance level. Subscale and Nurse Parent Support Tool scores did not differ between the groups. Overall, mothers reported more stress than fathers (p < 0.001). Conclusion Our study was unable to demonstrate the effect of person‐centred communication using the Guided Family‐Centred Care intervention. It may be necessary to replicate the design to address the risk of contamination and add instruments sensitive to human interaction.